1977
DOI: 10.1136/jech.31.3.141
|View full text |Cite
|
Sign up to set email alerts
|

Motor neurone disease and multiple sclerosis among immigrants to Britain.

Abstract: Hospital discharge rates for various immigrant groups resident in Greater London ahd the West Midlands were studied to compare the incidence of two diseases of the nervous system-motor neurone disease (MND) and multiple sclerosis (MS). For both these conditions immigrants from Europe, Ireland, America and from the old commonwealth countries of Canada, Australia, and New Zealand had discharge rates that were similar to those for people born in the United Kingdom. In contrast, immigrants from the new commonwealt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

1980
1980
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 4 publications
0
25
1
Order By: Relevance
“…West Indians had, therefore, about one fifth of the MS deaths expected at England and Wales rates confirming previous studies.' 2 …”
Section: Methodsmentioning
confidence: 99%
“…West Indians had, therefore, about one fifth of the MS deaths expected at England and Wales rates confirming previous studies.' 2 …”
Section: Methodsmentioning
confidence: 99%
“…New Commonwealth immigrants to England provided a fine opportunity to find out whether immigrants to England from areas of the world where MS was uncommon kept their low risk when they came to a country (England) where the disease was common. Tables VI-XI show the result of this study which was undertaken with support from the MS Society of Great Britain and Northern Ireland [12,13]. The studies in Greater London and the West Midlands showed that the immigrants from Asia.…”
Section: Westhmd and Kurlandmentioning
confidence: 99%
“…Analyses have revealed lower incidence of MND in the Japanese (0.69 per 100000) (Okumura et al, 1992) and in blacks (half the incidence of whites) (Lilienfield et al, 1989). It was also suspected that MND is less common among Indians and Pakistanis (Dean et al, 1977) and the assumption was then confirmed through the analysis of immigrants from these regions. Data demonstrated that MND is less common in these ethnic groups (Elian and Dean, 1993).…”
Section: Introductionmentioning
confidence: 99%